Apache administrator's handbook - Bowen, Rich (Developer's library., 2002)
The Apache Web server runs more than 55 percent of the sites on the Internet, making it the number one Web server, and more widely used than all other Web server combined. Apache 2.0 is the first majore release of Apache since its inception, and represents a complete change in Apache architecture--one requiring that administrators and developers learn new procedures and techniques for configuring and maintaining the Apache server. Apache Administrator's Handbook is a practical hands-on guide to the installation, configuration, and administration of the Apache Web server. It will show you how to build and configure Apache with the features and modules you need, how to seucre the server, how to interpret log files, and how to tune the server's performance. While aimed primarily at Apache server administrators, the book also contains information for developers interested in building dynamic Web sites on top of the Apache server using either CGI or mod_perl.